Teaching gender - Ferrebe, Alice; Tolan, Fiona (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2012)
"Encompassing feminism, masculinities and queer theory, and drawing on film, literature, language, creative writing and digital technologies, these essays, from scholars experienced in teaching gender theory in university English programmes, offer inventive and student-focused strategies for teaching gender in the twenty-first century classroom"--
Machine generated contents note: -- Introduction / A.Ferrebe & F.Tolan -- Gender and the Student Experience: teaching feminist writing in the post-feminist classroom / S. Andermahr -- Teaching English to Gender Students: collaborative encounters with print and digital texts / A.K.Naylor -- Teaching Queer Theory: Judith Butler, Shakespeare and She's The Man / C. Bates -- 'Do We Need Any More Books About Men?': teaching masculinities / B. Baker -- 'Men Couldn't Imagine Women's Lives': teaching gender and creative writing / S. Earnshaw -- Teaching Gender and Language / J. Sunderland -- Teaching Gender and Popular Culture / S. Genz -- Bodies, Texts and Theories: teaching gender theory in a postcolonial context / S. L. Welsh -- The Space Between Submission and Revolution: teaching gender in China / C. M.Voskuil -- Teaching Gender in a Turkish Context / R. K.Silku -- Women's Studies, Gender Studies, Feminist Studies? designing and delivering a course in gender at postgraduate level / R. Ballaster -- Further Reading -- Index.
Includes bibliographical references and index.
Keywords: Gender identity in literature; Sexual orientation in literature; Sex role in literature; Feminism and literature; Gender identity in education; Women's studies; Men's studies; LITERARY CRITICISM / Semiotics & Theory; LITERARY CRITICISM / Feminist; SOCIAL SCIENCE / Gender Studies; Geschlechterforschung; Hochschulunterricht; Aufsatzsammlung